Photodegredation of Schiff Bases Copper(II) Complexes in Dimethyl Sulphoxid (DMSO) - AL-Lami, A.J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Photodecomposition of dichlorobis N [4-Azo benzene aniline)2-hydroxy benzilidene] Copper (II) (Complexe A1) and dichloro N[2-Azo 3- sulphonic -2- naphthol) 6- carboxylic 2- hydroxy benzilidene] copper (II) (Complex A2).have been performed at  Î» = 373 nm for complex A1and at Î» = 358 nm for complex A2 in dimethyl sulphoxide at 25Câ—¦. the absorbance spectrum of these complexes  have been recorded with time of irradiation in order to examine the kinetics of photodecay. The apparent rate constant (Kd) for the first order reaction has been calculated and found to be 1.1 Ã—10-2 min-1 for complexe A1 and 2.34 Ã— 10-2 min-1 for camplexe A2. the primary quantum yields (Ã˜ ) has also been calculated and found to be 2.810Ã—10-1 and  0.2765 Ã—10-1 for complex A1 and A2  respectively